Sequential Association Rule Mining for Autonomously Extracting Hierarchical Task Structures in Reinforcement Learning - Behzad Ghazanfari; Fatemeh Afghah; Matthew E. Taylor (IEEE Access, 2020)
Reinforcement learning (RL) techniques, while often powerful, can suffer from slow learning speeds, particularly in high dimensional spaces or in environments with sparse rewards. The decomposition of tasks into a hierarchical structure holds the potential to significantly speed up learning, generalization, and transfer learning. However, the current task decomposition techniques often cannot extract hierarchical task structures without relying on high-level knowledge provided by an expert (e.g., using dynamic Bayesian networks (DBNs) in factored Markov decision processes), which is not necessarily available in autonomous systems. In this paper, we propose a novel method based on Sequential Association Rule Mining that can extract Hierarchical Structure of Tasks in Reinforcement Learning (SARM-HSTRL) in an autonomous manner for both Markov decision processes (MDPs) and factored MDPs. The proposed method leverages association rule mining to discover the causal and temporal relationships among states in different trajectories and extracts a task hierarchy that captures these relationships among sub-goals as termination conditions of different sub-tasks. We prove that the extracted hierarchical policy offers a hierarchically optimal policy in MDPs and factored MDPs. It should be noted that SARM-HSTRL extracts this hierarchical optimal policy without having dynamic Bayesian networks in scenarios with a single task trajectory and also with multiple tasks' trajectories. Furthermore, we show theoretically and empirically that the extracted hierarchical task structure is consistent with trajectories and provides the most efficient, reliable, and compact structure under appropriate assumptions. The numerical results compare the performance of the proposed SARM-HSTRL method with conventional HRL algorithms in terms of the accuracy in detecting the sub-goals, the validity of the extracted hierarchies, and the speed of learning in several testbeds. The key capabilities of SARM-HSTRL including handling multiple tasks and autonomous hierarchical task extraction can lead to the application of this HRL method in reusing, transferring, and generalization of knowledge in different domains.